Effect of Speed and Current on Welding Defect for Low Carbon Steel Using Metal Inert Gas (MIG) Welding (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Metal inert gas welding process is usually controlled by many variables. The research aims to study two of these variables  (speed and current) on welding defects by changing one and fixing the others then doing the tests, which have included visual test, the fluid penetration test and optical microscope. The process of inert gas welding was done within a current ranging from (260-266-272) A and feeding speed (110-115-120) in/min. The results of the visual inspection showed defects such as overlap, spark, incomplete welding area and lack of homogeneity due to incompatibilities between current and feeding speed. The best results with lowest defects were within current 272 A and speed 115 in/min. The examination of the liquid penetrating showed some cracks resulting from the temperature difference, while the microscopic examination showed the effect of current on the heat of welding area and thus the microscopic structure of the samples.